2017
DOI: 10.3390/nu9030301
|View full text |Cite
|
Sign up to set email alerts
|

Association between Circulating Vitamin D Level and Urolithiasis: A Systematic Review and Meta-Analysis

Abstract: Many studies compared the serum/plasma 1,25 dihydroxyvitamin D3 (1,25(OH)2D) and 25 hydroxyvitamin D3 (25(OH)D) between people with and without nephrolithiasis, and their results were conflicting. After systematically searching PubMed, Web of Science, The Cochrane Library, CNKI, and the Wanfang Database, we conducted a meta-analysis. Thirty-two observational studies involving 23,228 participants were included. Meta-analysis of these studies showed that of stone formers (SFs), calcium SFs had significantly high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 60 publications
0
26
0
3
Order By: Relevance
“…26,27 Table 1 does not include conditions where the elevation in plasma levels of 1,25(OH) 2 D is merely associated with the condition, rather than being a result of the condition. For example, elevation in 1,25(OH) 2 D is a risk factor for kidney stones, 49 and kidney stones have significant comorbidity with CD. 50 However, since there is no evidence that kidney stones cause the elevation in plasma levels of 1,25(OH) 2 D that is associated with them, 49 kidney stones are not included in Table 1.…”
Section: Conditions That Cause Elevated 125(oh) 2 D and Cd Riskmentioning
confidence: 99%
See 1 more Smart Citation
“…26,27 Table 1 does not include conditions where the elevation in plasma levels of 1,25(OH) 2 D is merely associated with the condition, rather than being a result of the condition. For example, elevation in 1,25(OH) 2 D is a risk factor for kidney stones, 49 and kidney stones have significant comorbidity with CD. 50 However, since there is no evidence that kidney stones cause the elevation in plasma levels of 1,25(OH) 2 D that is associated with them, 49 kidney stones are not included in Table 1.…”
Section: Conditions That Cause Elevated 125(oh) 2 D and Cd Riskmentioning
confidence: 99%
“…For example, elevation in 1,25(OH) 2 D is a risk factor for kidney stones, 49 and kidney stones have significant comorbidity with CD. 50 However, since there is no evidence that kidney stones cause the elevation in plasma levels of 1,25(OH) 2 D that is associated with them, 49 kidney stones are not included in Table 1.…”
Section: Conditions That Cause Elevated 125(oh) 2 D and Cd Riskmentioning
confidence: 99%
“…The impact of vitamin D supplementation (without calcium) has been studied in small prospective studies and found to be safe for the average KSF with vitamin D deficiency [105]. However, a subset of calcium stone formers may exhibit worsening hypercalciuria upon vitamin D supplementation [106]. In his presentation Dr Maalouf reviewed the epidemiology and pathophysiologic mechanisms by which calcium and vitamin D supplements impacts nephrolithiasis risk, and outlined a framework to employ when considering calcium and/or vitamin D supplementation in nephrolithiasis patients (Table 3).…”
Section: Nephrolithiasis From Vitamin D and Calcium Supplementationmentioning
confidence: 99%
“…23 Serum vitamin D düzeyindeki yükseklik ile böbrek taşı gelişimi arasında ilişki bulunmamıştır. 24,25 Hastalarımızın günlük vitamin D alımı 25,9±10,6 (7,4) μg/gün olup kan 25(OH) vitamin D düzeyi 8 hastada >30 ng/ mL, 13 hastada 20-30 ng/mL ve 9 hastada <20 ng/mL idi. Hastalarımız arasında hiperkalsiüriye neden olacak vitamin D yüksekliği olan hasta bulunmamakta idi.…”
Section: Discussionunclassified